External jugular vein aneurysm presenting as submandibular neck mass. Issue 5 (31st May 2022) - Saleem, Matthew I; Tham, Tristan; Diaz, Anise M; Keating, Patrick; Georgolios, Alexandros
Abstract: External jugular vein aneurysms presenting as neck masses is very rare in the literature. This case report presents an 80-year-old female, who was referred to the office due to an incidental finding of a left submandibular neck mass. The patient presented to her primary care physician initially complaining of bilateral intermittent ear pain that was present for several years. After extensive workup, the patient was diagnosed with a left external jugular vein aneurysm. When asymptomatic, this rare condition can be followed safely on an outpatient basis. Vascular surgery consultation should also be considered.